2022
DOI: 10.1038/s41598-022-23957-5
|View full text |Cite
|
Sign up to set email alerts
|

Salivary parameters and periodontal inflammation in obstructive sleep apnoea patients

Abstract: The aim of this cross-sectional study was to objectively assess the salivary flow rate and composition and periodontal inflammation in obstructive sleep apnoea (OSA) patients. The subjects, who underwent whole-night polysomnography or polygraphy, were referred for saliva sampling and periodontal examination. According to the severity of OSA based on the Apnoea Hypopnea Index (AHI) value, the subjects were classified into groups: no OSA (AHI < 5; N = 17), mild to moderate OSA (AHI 5–29.9; N = 109), and sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Report from a previous study indicated that SFR in patients with periodontitis significantly decreased, almost twofold, as compared to healthy controls 44 . Additionally, significantly higher concentration of electrolytes and decreased pH were observed in periodontitis patients with hyposalivation and reduced salivation as compared to subjects with normal salivation 45 . Similarly, patients with stage IV periodontitis exhibited acidic pH and significantly reduced SFR 46 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Report from a previous study indicated that SFR in patients with periodontitis significantly decreased, almost twofold, as compared to healthy controls 44 . Additionally, significantly higher concentration of electrolytes and decreased pH were observed in periodontitis patients with hyposalivation and reduced salivation as compared to subjects with normal salivation 45 . Similarly, patients with stage IV periodontitis exhibited acidic pH and significantly reduced SFR 46 .…”
Section: Discussionmentioning
confidence: 91%
“…44 Additionally, significantly higher concentration of electrolytes and decreased pH were observed in periodontitis patients with hyposalivation and reduced salivation as compared to subjects with normal salivation. 45 Similarly, patients with stage IV periodontitis exhibited acidic pH and significantly reduced SFR. 46 Although passive drooling technique is widely used for collecting salivary samples, further standardization is advised.…”
Section: Discussionmentioning
confidence: 98%
“…These findings may indicate that TFF3 is upregulated in the inflammatory mucous epithelium of the gastrointestinal tract and oral mucosa. A previous study found that patients with mild to moderate OSA and severe OSA had significantly higher proportions of plaques versus the control group (59% and 73% vs. 38%; p = .001) (Tranfić Duplančić et al, 2022). Dental plaques, containing over 700 bacteria, lead to local inflammation resulting in higher TFF3 levels in patients with OSA (Gao et al, 2018;Murakami et al, 2018;Paul et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Xerostomia is often associated with mouth breathers and can predispose to caries and periodontal disease through complete or partial reduction of protective salivary flow to portions of the dentition during sleep or during the day. OSA and periodontal disease share some of the same risk factors and it is not uncommon to see a greater periodontal disease prevalence in patients with OSA [40]. Common risk factors may include obesity, gender, male more than female, age, smoking and mouth breathing resulting in xerostomia, and alcoholism.…”
Section: Oral-related Conditions Associated With Osamentioning
confidence: 99%
“…Duplancic and colleagues, evaluating salivary parameters and periodontal inflammation in OSA patients, showed that patients with hyposalivation and reduced salivation had higher concentrations of salivary electrolytes and lower salivary pH than subjects with normal salivation and that patients with severe OSA tended to have a higher clinical attachment levels and plaque volume. The authors noted that multiple interactions might impact salivary flow and electrolyte composition and that complex interrelationships might affect the integrity of oral health, especially considering OSA severity, inflammation, concomitant diseases and medication [40].…”
Section: Stop-bang Sleep Apnea Questionnairementioning
confidence: 99%